Emotions in rituals and performances
1 online resource (x, 460 pages)
Keywords: Challenging the idea that rituals are static and emotions irrational, the volume explores the manifold qualities of emotions in ritual practices. Focusing explicitly on the relationship between emotions and rituals, it poses two central questions. First, how and to what extent do emotions shape rituals? Second, in what way are emotions ritualized in and beyond rituals? Strong emotions are generally considered to be more spontaneous and uncontrolled, whereas ritual behaviour is regarded as planned, formalized and stereotyped, and hence less emotional. However, as the volume demonstrates, rituals often reveal strong emotions among participants, are motivated by feelings, or are intended to generate them. The essays discuss the motivation for rituals; the healing function of emotions; the creation of new emotions through new media; the aspect of mimesis in the generation of feelings; individual, collective, and non-human emotions; the importance of trance and possession; staged emotions and emotions on stage; emotions in the context of martyrdom; emotions in Indian and Western dance traditions; emotions of love, sorrow, fear, aggression, and devotion. Furthermore, aesthetic and sensory dimensions, as well as emic concepts, of emotions in rituals are underscored as relevant in understanding social practice.